Concerto para viola e orquestra de cordas de Radamés Gnattali: uma análise das implicações de performance nas decisões interpretativas - Ana Cielo Guerra (2017)
This work presents a historical and interpretative study of the concerto, an investigation of the musical text, video and recording, as well as an analysis of interpretive ideas of four viola professors/soloist who have performed this concerto and a edition review of the viola part. We search an understanding of compositional processes in order to obtain a relevant interpretation of the concerto with the identification of musical influences in the style of the composer Radames Gnattali and the musical ideas of the viola professors. There are in the literature of this composer some musical influences such as tango, seresta, carnival march and jazz. The identification of the presence of these elements and their importance in the constitution of the concerto, as well as the understanding of the interpretative decisions of the performer violist, and an edition proposal of the viola part, are the results of this research.